UNDERSTANDING BUYING BEHAVIOUR AND AWARENESS OF STUDENTS REGARDING PLASTIC USAGE - Singh, Pratima; Meghna; Farkya, Sunita; Atheya, Ritu (SCHOOL SCIENCE, 2025)
Plastic—‘a miracle material’, has become an indispensable part of our life, and living without it may pose significant challenges and difficulties. In spite of many advantages attached to it, plastic is a serious environmental threat and its disposal has become a cause of concern worldwide. It has reached even the remotest areas on earth in the form of microplastics—in the Arctic, on glaciers, in oceans and rivers, severely affecting terrestrial and aquatic ecosystems. In order to preserve the fine balance of ecosystems, it is extremely important to create awareness and educate students regarding the importance of environmental conservation and eliminating plastic usage from our daily lives. The present research was carried out to understand the buying behaviour and awareness of students regarding plastic usage at household level. Information was sought about common sources of plastic waste generation due to lifestyle choices. The study also tried to suggest strategies to reduce plastic usage and adopting plastic waste segregation at source. The study also focuses on the need to create awareness through integrated programme-based approaches at schools, homes and communities to eliminate single-use plastic from the environment